(untitled) (Journal of Pharma Insights and Research, 2025)
A prospective epidemiological study was conducted over six months to investigate the incidence, risk factors, and outcomes of sepsis in patients aged 30-90 years at Apollo Hospital, Kakinada. The study enrolled 80 patients diagnosed with sepsis, comprising 42 males and 38 females. Data collection included demographics, comorbidities, clinical interventions, and microbiological profiles. The highest prevalence was observed in the 70-80 years age group. Hypertension (77.5%) and diabetes mellitus (57.5%) were the predominant comorbidities. Severe pneumonia emerged as the leading cause of sepsis (36.25%), followed by acute pyelonephritis (16.25%) and septic shock (12.5%). Blood cultures revealed various pathogens including E. coli, Klebsiella pneumoniae, and coagulase-negative staphylococci, though 58.75% showed no growth. The study documented an 81.25% survival rate, with 18.75% mortality. Inflammatory markers like C-reactive protein and procalcitonin were elevated in most patients, indicating severe systemic inflammation. The results of this study show the significant impact of age and comorbidities on sepsis development and outcomes. Early identification of infection sources and appropriate antibiotic administration based on culture sensitivity improved patient outcomes, though mortality remained substantial in patients with multiple risk factors.